The Child-Friendly School Policy Implementation - Yenuri, Ali Ahmad; Aminuddin, Ahmad; SM, M. Mujibudin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to encourage the implementation of the Child-Friendly School (CFS) policy at the Senior High School (SMA) level in East Java Province by highlighting supporting and inhibiting factors, the impact of the policy on the school environment, and strengthening strategies. The study used a mixed-methods approach with a descriptive design. Data were obtained from three schools selected purposively: SMAN 8 Malang, SMAN 20 Surabaya, and SMAN 1 Trenggalek. Data sources included principals, teachers, students, parents, and school policy documents. Data collection techniques included in-depth interviews, participant observation, questionnaires, and document analysis. Data were described thematically and descriptively to reveal the dynamics of policy implementation. The results showed that most schools had integrated CFS values such as non-discrimination, religious tolerance, and bullying prevention efforts. However, challenges were still found, including seniority practices that lead to bullying, limited facilities in rural areas, and a weak bullying case reporting system. It is proven that the implementation of the Child-Friendly School policy has shown significant progress in East Java, but the desire and equality of the quality of its implementation still need to be strengthened. The involvement of all parties, such as teachers, students, parents, and the government, is an important key in creating a school environment that is truly safe, inclusive, and supports the holistic development of children.